2019
DOI: 10.1021/acs.jpcc.9b00259
|View full text |Cite
|
Sign up to set email alerts
|

DFT-GIPAW 27Al NMR Simulations for Intermetallics: Accuracy Issues and Magnetic Screening Mechanisms

Abstract: This study reports first-principles simulations of 27Al solid-state nuclear magnetic resonance (ssNMR) shifts (δiso exp) carried out for a set of seven Al-containing intermetallic compounds. With the aim of assessing accuracy issues in such calculations using the gauge-including projector augmented waves method, the referred set was sought to cover the wide range of experimental 27Al δiso exp shifts reported in the literature for this type of compound in a representative way (from about −200 to 1600 ppm). From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…DFT calculations on binary intermetallic aluminum compounds showed that, for example, in VAl 3 and TiAl, the orbital contribution gets surpassed by the spin contribution, leading to an overall negative NMR shift. In CuAl 2 , for example, both contributions point in the same direction . It is interesting to note that metal–organic Al­(I) compounds like Cp*Al (δ = −150 ppm), (C 5 H 2 (SiMe 3 ) 3 )Al (δ = −165 ppm), or (C 5 H 3 (SiMe 3 ) 2 )Al (δ = −168 ppm) reported by Schnöckel and co-workers also show negative chemical shifts .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…DFT calculations on binary intermetallic aluminum compounds showed that, for example, in VAl 3 and TiAl, the orbital contribution gets surpassed by the spin contribution, leading to an overall negative NMR shift. In CuAl 2 , for example, both contributions point in the same direction . It is interesting to note that metal–organic Al­(I) compounds like Cp*Al (δ = −150 ppm), (C 5 H 2 (SiMe 3 ) 3 )Al (δ = −165 ppm), or (C 5 H 3 (SiMe 3 ) 2 )Al (δ = −168 ppm) reported by Schnöckel and co-workers also show negative chemical shifts .…”
Section: Resultsmentioning
confidence: 80%
“…In CuAl 2 , for example, both contributions point in the same direction. 118 It is interesting to note that metal−organic Al(I) compounds like Cp*Al (δ = −150 ppm), (C 5 H 2 (SiMe 3 ) 3 )Al (δ = −165 ppm), or (C 5 H 3 (SiMe 3 ) 2 )Al (δ = −168 ppm) reported by Schnockel and co-workers also show negative chemical shifts. 119 This extreme shielding was explained by significant π-bonding interactions between the Al and the ligand and therefore an energetic separation between the HOMO and LUMO.…”
Section: Solid Solution and Crystal Chemistrymentioning
confidence: 94%
“…Thus, in the framework of planewaves DFT, a gauge including the projected augmented wave [2,3] (GIPAW) method was introduced to calculate nuclear resonance magnetic (NMR) parameters in solids, avoiding all-electron calculations. In the GIPAW approach [4,5], a uniform magnetic field is applied using boundary conditions, a periodic magnetic field with a finite wavelength r G is the gauge origin and is subsequently extrapolated in the limit r G → 0 to compute the chemical shielding. This formalism was seen to manage the numerical instabilities associated with the summation of two divergent terms and with the generalized gradient approximation exchange-correlation functional (the method of choice for condensed-matter simulations) to perform accurate results [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%